Strengthening of Reinforced Concrete slabs using macro and micro synthetic fibers. (May 2023) - S. Zainal, S.M. Iqbal; Hejazi, Farzad; Mafaileh, Ala M.A.
Abstract: Concrete is brittle and prone to cracking, especially under tensile forces. The gradual development and propagation of cracks would subsequently lead to brittle failure. The use of fibers is effective in restricting the propagation of cracks and improving the failure mode of cement composites. This study attempts to enhance the performance of Reinforced Concrete (RC) slabs under a four-point bending test by embedding synthetic fibers with distinct parameters. In the preliminary stage, experimental uniaxial tests were conducted in compression and tension to observe the stress–strain behavior of the developed Hybrid Fiber Reinforced Concrete (HyFRC). The obtained data are then used as input in Finite Element (FE) modeling for numerical analyses. In the primary stage, the numerical results were verified from the experimental data with respect to cracking behavior, ultimate load capacity, corresponding mid-span deflection, and steel reinforcement strain output. Based on the results, the HyFRC slabs exhibited positive improvements in terms of load-carrying capability by reducing stress in the concrete and rebars. The HyFRC slabs also experienced lower deflections with improved crack resistance and high flexural stiffness than the control slab. Additionally, the developed FE models presented a low margin of error compared to the experimental data for all assessed criteria.